Nasi miedzy oceanami - Budrewicz, Olgierd (Warszawa : Wydawn. Polonia, 1987)
Vignettes of famous and not so famous Polish immigrants in the US, Canada and Australia.
Keywords: Polish people -- Foreign countries -- Biography